The impact of social support and emotion dysregulation on COVID-19 depressive symptoms - Dhruve, Deepali M.; Russo, Jenna E.; Oliveros, Arazais D. (Frontiers in Psychology, 2023)
Stress resulting from the global COVID-19 pandemic has been linked to psychological consequences, such as depressive symptoms, for individuals worldwide. Outbreaks and pandemics are known to accentuate stressors or generate new ones owing to health-related worries, reduced mobility and social activity due to quarantine, and sudden life changes. Although post-lockdown U.S. research findings suggest a greater risk of depression among 18-to 25-year-olds, familiarity with technology and virtual socializing may offer college students some protective effect, warranting research with such groups. The current study thus explored emotion dysregulation (ED) and perceived social support (PSS) as potential mechanisms for the relation between COVID-19 stress and depressive symptoms among students at a Southern university in the United States. Participants (N = 489) completed a cross-sectional survey assessing their current levels of COVID-19 stress, ED, PSS, and depressive symptoms. Path analysis showed that PSS buffered the effect of ED on depressive symptoms. Results support the explanatory role of ED in the relation between COVID-19 stress and depressive symptoms. Perceived social connection may be an essential factor for psychological outcomes during periods of stress and isolation, particularly for those reporting high ED.